2021
DOI: 10.3390/ma14010229
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Shear and Particle Crushing Characteristics in Ring Shear System Using the PFC2D

Abstract: The shear and particle crushing characteristics of the failure plane (or shear surface) in catastrophic mass movements are examined with a ring shear apparatus, which is generally employed owing to its suitability for large deformations. Based on results of previous experiments on waste materials from abandoned mine deposits, we employed a simple numerical model based on ring shear testing using the particle flow code (PFC2D). We examined drainage, normal stress, and shear velocity dependent shear characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The PFC particle program analyzes the change in force and displacement of each particle, calculates each particle's displacement according to Newton's second law, and then generates an overall model of the internal distribution of stress-strain, crack extension, and other rules of change. Figure 17 displays the PFC model solution procedure [35][36]. the instant o t may be calculated using Newton's second law, and they are, respectively:…”
Section: Software Calculation Principlesmentioning
confidence: 99%
“…The PFC particle program analyzes the change in force and displacement of each particle, calculates each particle's displacement according to Newton's second law, and then generates an overall model of the internal distribution of stress-strain, crack extension, and other rules of change. Figure 17 displays the PFC model solution procedure [35][36]. the instant o t may be calculated using Newton's second law, and they are, respectively:…”
Section: Software Calculation Principlesmentioning
confidence: 99%
“…The shear and particle-crushing characteristics of the failure plane (or shear surface) in catastrophic mass movements are examined with a ring shear apparatus, which is generally employed owing to its suitability for large deformations [ 45 ]. Based on the results of previous experiments on waste materials from abandoned mine deposits, we employed a simple numerical model based on ring shear testing using the particle flow code (PFC 2D ).…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
“…The frictional work at peak and the residual shear stresses ranged from 303 kPa·s to 2579 kPa·s for the given drainage and normal stress conditions. These results showed that clump particles were partially crushed at peak shear stress [ 45 ].…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
“…Several researchers have conducted calibration chamber and centrifuge tests on carbonate sands to better understand what happens when a pile is driven into weak sands [ 5 , 6 , 7 , 8 ]. This phenomenon has also attracted many researchers to conduct laboratory tests to study the influence of particle breakage on the critical state behaviors, shear stress ratios and dilatancy of granular soils [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] as well as numerical modeling [ 14 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies of direct shear tests at the microscopic level have become more popular using the Discrete Element Method among others by [ 14 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Seyyedan et al [ 29 ] employed a novel approach that combined the Discrete Element Method (DEM) and Extended Finite Element Method (XFEM) to conduct numerical simulations of direct shear tests.…”
Section: Introductionmentioning
confidence: 99%